2005
DOI: 10.1116/1.2127943
|View full text |Cite
|
Sign up to set email alerts
|

Mask defect inspection using an extreme ultraviolet microscope

Abstract: A defect inspection technique on an extreme ultraviolet lithography mask is described. There are two kinds of defects, amplitude defects and phase defects due to the multilayer coating. The technique utilizes a microscope using the same 13.5 nm wavelength as the light used for exposure, and producing a magnified image of defects on a mask. Using this microscope, amplitude defects on practical masks and phase defects are observed. A phase defect was formed by a multilayer coated on a line pattern with a height … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…Extreme ultraviolet lithography (EUVL) is a strong candidate for the next lithography technology generation to achieve 32 nm nodes or smaller by utilizing a light of 13.4 nm wavelength (Gullikson, Tejnil, Liang, & Stivers, 2004;Hamamoto et al, 2005;Kim, Chang et al, 2006;Yan, He, Ma, & Orvek, 2006). Every EUVL mask must be assured of being free of particles prior to scanning exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Extreme ultraviolet lithography (EUVL) is a strong candidate for the next lithography technology generation to achieve 32 nm nodes or smaller by utilizing a light of 13.4 nm wavelength (Gullikson, Tejnil, Liang, & Stivers, 2004;Hamamoto et al, 2005;Kim, Chang et al, 2006;Yan, He, Ma, & Orvek, 2006). Every EUVL mask must be assured of being free of particles prior to scanning exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Extreme ultraviolet lithography (EUVL), which is considered a strong candidate for the next lithography technology generation, utilizes radiation of very short wavelength of 13.4 nm to achieve 32-nm nodes or smaller [1], [2]. EUVL masks need to be protected against all particles larger than approximately 30 nm in the case of 32-nm node manufacturing [3].…”
Section: Experimental Investigations On Particle Contamination Of Masmentioning
confidence: 99%
“…We demonstrated that a phase defect with a width of 90 nm and a depth of 5 nm was printable. 3 Furthermore, in 2007 our research group made smaller programed phase defects and demonstrated that the critical size for printable defects in a multilayer on a glass substrate was a width of 75 nm and a depth of 2 nm. 4 This result agrees well with the results of resist replication tests obtained with the microexposure tool ͑MET͒ at the Lawrence Berkeley National Laboratory ͑LBNL͒.…”
Section: Introductionmentioning
confidence: 99%